Public Shells. - Morgan, Alfred Powell (1991)
Keywords: dept.fin; faculty_collection; sabbatical_report

Non-linear characteristics of the sterling/european currency unit exchange rate: 1984–1992 - Chappell, D.; Eldridge, R.M. (International Journal of Phytoremediation, 1997)
The behaviour of the Sterling/European Currency Unit (ECU) exchange rate is examined both during the time before Britain joined the European exchange rate mechanism (ERM) and during the time of Britain's membership. During the latter period, a GARCH (1, 1) model fits the data well but during the pre-ERM period there is evidence of significant non-linear - possibly chaotic - structure in the GARCH residuals. Analysis of the dominant Lyapunov exponents and correlation dimension for the pre-ERM period suggests that the data generation process may be chaotic and this is reinforced by the highly significant BDS statistics obtained for this sample period. © 1997, Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31]
Keywords: Non-linearity; Sterlingecu exchange rate; dept.eco; dept.fin

Rates of return on art objects, the fisher hypothesis, and inflationary expectations - Matsumoto, Keishiro; Andoh, Samuel K; Hoban, James P (The Financial Review, 1994)
After surveying the evolution of the major methodologies in inflation hedging, this study presents a unique methodology that uses principal component factor analysis to separate the effects of variability in the real rate of return from the nominal rate of return. This approach allows the effects of both anticipated and unanticipated inflation on rates of return to be estimated more precisely. This study finds that art objects perform well in terms of average real rates of return and that the market, though not perfect, integrates anticipated inflation into the rates of return. However, unanticipated inflation is very often negatively related to the rates of return. Copyright © 1994, Wiley Blackwell. All rights reserved
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/022-870-118-937-067 tex.type: [object Object]
Keywords: dept.eco; dept.fin

Controlled chain reaction as a regulatory technique - Bodo, Peter (International Advances in Economic Research, 1996)
This paper discusses a regulatory technique that consists of the use of a controlled chain reaction to influence social and economic processes. It claims that this method was employed by Hungarian control agencies to further centralize the farm sector in the 1970s. Section I of the paper presents three versions of this technique. Section II shows how the institutional structure of Hungarian agriculture made the application of this technique possible. (JEL P21).
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/075-380-606-287-914 tex.type: [object Object]
Keywords: dept.eco; dept.fin

The effect of zoning on housing construction - Thorson, James A (Journal of Housing Economics, 1997)
This paper examines whether a more restrictive zoning ordinance actually reduces construction of new housing. This may seem at first to be a trivial issue, since why else would a zoning board make the ordinance more restrictive. However, it is possible for landowners to circumvent the zoning law. For example, they can subdivide their land before the zoning change occurs. In addition, they can bargain with the local zoning officials and offer side payments, also known as exactions, for the right to develop their land. This paper examines a famous case of agricultural downzoning in McHenry County, Illinois. It finds that although the number of building permits issued did not fall immediately, in the long run the number of permits issued by the county was significantly reduced. This suggests that developers were able to anticipate the zoning change and subdivide their land before it occurred. (C) 1997 Academic Press.
31 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/024-739-138-771-737 tex.type: [object Object]
Keywords: dept.eco; dept.fin

An examination of the monopoly zoning hypothesis - Thorson, J.A. (Land Economics, 1996)
There have been several studies that have investigated the effect of zoning on housing prices. One hypothesis is that the restrictiveness of zoning laws will vary with the monopoly power of a town. The degree of monopoly power varies with the number of towns in the urban area. Urban areas with few zoning jurisdictions are likely to have higher housing prices than more fragmented urban areas. Previous research on this topic has shown mixed results. The results in this article suggest that towns with more monopoly power do tend to have significantly higher housing prices than more fragmented urban areas.
23 citations (Crossref) [2023-10-31]
Keywords: dept.eco; dept.fin